2021
DOI: 10.3390/en14185654
|View full text |Cite
|
Sign up to set email alerts
|

From Clothing Rations to Fast Fashion: Utilising Regenerated Protein Fibres to Alleviate Pressures on Mass Production

Abstract: Sustainable methods of practice within the fashion and textile industry (FTI) often strive to employ a circular economy that aims to eliminate waste through the continual use of resources. Complex problems such as waste, consumption, and overproduction are heavily intertwined; the main aim of this paper is to report on research focused on re-examining the potential of food waste streams as a commercially viable and circular source of raw materials for the FTI. Herein, regenerated protein fibres (RPFs) from foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Customers were also not as keen to buy Ardil as ICI had hoped, with sales failing to grow. The struggle for new and experimental fibres to be accepted into a wider market is an important lesson to be taken forward into contemporary RPF development; the inherent poor fibre strength that plagued manufacturers at the time could now be seen as an opportunity, aligning RPFs with alternative, faster fashion cycles [77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Customers were also not as keen to buy Ardil as ICI had hoped, with sales failing to grow. The struggle for new and experimental fibres to be accepted into a wider market is an important lesson to be taken forward into contemporary RPF development; the inherent poor fibre strength that plagued manufacturers at the time could now be seen as an opportunity, aligning RPFs with alternative, faster fashion cycles [77].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the majority of the milk being wasted in the UK is being generated in homes (90%), which would give rise to logistical problems for collection and ensuring that a uniform feedstock is obtained [79]. Casein-based RPFs were pioneered within Europe at roughly the same time as Ardil, with fibres such as Lanital having a similarly short-lived lifetime during and after WW2, although more contemporary research has been conducted into casein-based fibres [77].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that demographic growth has influenced the availability of resources globally due to the increase in the consumption of disposable goods, leading to potential excessive levels of consumption and the generation of waste [ 9 ]. In the manufacturing context, the textile sector raises concerns about the abundant use of natural resources and of fossil derived materials that raise environmental and social problems due to the manufacturing and discarding of textile clothing [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, several studies have demonstrated the existence of efforts to change the perception about the textile waste which is generated throughout the production chain, addressing several good practices that are environmentally friendly [ 20 ]. Such practices are related to the development of materials from waste [ 5 , 14 , 19 , 22 , 23 , 24 ], the recycling of textiles [ 12 , 20 , 25 , 26 , 27 ], and the development of textile fibers from non-textile waste, among others [ 7 , 8 , 9 , 28 ]. Table 1 offers an overview of the literature addressing the textile industry and the approaches related to economic and environmental aspects that hold opportunities for the circular economy.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent Special Issue article, Stenton et al [11] pointed to the importance of using regenerated protein fibers to reduce the pressure on mass production. The key aim of the analyses presented in the article was to link quality and durability in the context of a local circular fashion economy, where the analysis of textile quality and the life cycle is holistically matched to the durability of the materials in order to reduce the amount of waste.…”
mentioning
confidence: 99%